The experience of trauma resuscitation in the emergency department: A patient perspective. - O'Brien, Jo-Anne Elizabeth. (University of Ottawa (Canada), 2002)
Traumatic injury occurs without warning leaving no time to prepare. The patient may be frightened about the unknown, their future, or the prognosis. The patient arrives in the Emergency Department (ED) where assessment and management of injuries begins. Little is known about the patient's experience of trauma resuscitation. Therefore, a qualitative study using interpretive phenomenology was undertaken to describe the lived experience of trauma resuscitation in the ED. A total of seven participants were interviewed after they experienced trauma resuscitation in the ED of a Lead Trauma Hospital. Tape-recorded interviews were conducted on the in-patient Trauma Unit between day 2 and day 7 post trauma resuscitation. Follow-up interviews were conducted with four participant's seven to twelve months after the initial interview. Data analysis utilized Colaizzi's eight-step analytical process. Four themes were revealed in the data analysis: I Remember, I Was Scared, I Felt Safe, and I Will Be OK. The findings also revealed that initial perceptions of vulnerability subsided as a sense of feeling safe became prominent. System factors were acknowledged to influence the overall conviction that it was a positive experience. Lastly, nursing interventions were important in contributing to the participants' feelings of being safe. This suggests that comfort care measures need to be at the forefront of trauma nursing care as well as measures aimed at attaining physiological stability.
Keywords: Health Sciences, Nursing.